Evaluation of mustard (Brassica juncea) and barley (Hordeum vulgare) based cropping sequence under variable irrigation supplies - KAUR, ANUREET; SEKHON, K S; THAMAN, S; SIDHU, A S; BUTTAR, G S (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted at Regional Station, Bathinda during 2010-2013 to evaluate various crop sequences under variable irrigation regimes. The experiment was conducted in split plot design with six crop sequences, viz. barley-Bt cotton, barley-cluster bean, barley-green gram,mustard-Bt cotton, mustard-cluster bean and mustardgreen gram in main plots and three irrigation regimes [optimum (O), sub-optimum (SO) and sub-sub optimum (SSO) ] were kept in sub plots with three replications. The grain yield of barley reduced significantly where grown after cotton to the tune of 10.8 and 9.2% as compared to green gram and cluster bean, respectively. The barley grain equivalentyield (BGEY) was higher in mustard under all the preceding crops (cotton, green gram and cluster bean).Significant increase in cotton equivalent yield (CEY) was noticed in cotton sown after barley than mustard. Amongst the CEY of the system, barley-cotton crop sequence gave significantly highest CEY which was at par with mustard-clusterbean and mustard-cotton crop sequence. Significantly higher barley grain yield, mustard grain yield and cotton equivalent yield was recorded in optimum water regime, followed by SO and lowest in SSO regime. Water expense efficiency (WEE) of barley was higher preceding greengram followed by cluster bean and lowest in cotton system. Whereas,WEE was almost same under mustard succeeding cotton and greengram but was lowest in mustard-cluster bean crop sequence. The maximum water productivity (WP) was recorded in clusterbean- mustard followed by clusterbeanbarley crop sequence. The sub-sub-optimum irrigation regime recorded highest WP followed by SO and lowest in optimum. The highest organic carbon was observed under cluster bean-barley followed by cluster bean-mustard cropping system. The potassium content deceased in cotton based crop sequence as compared to cluster bean and greengram crop sequence. Whereas, increase in available N, and P was noticed in cluster bean and green gram based cropping systems than cotton based sequence. The highest cost of cultivation was recorded in cotton based cropping sequences and lowest in cluster bean based cropping sequences. Consequently, higher net returns, B: C ratio were obtained in clusterbean based crop sequence than cotton based sequence.The optimum water regime showed highest gross returns, net returns and benefit cost ratio.